2-Dimensional Reversible Hexagonal Cellular Automata with Periodic Boundary - Uguz, S.; Siap, I.; Akin, H. (POLISH ACAD SCIENCES INST PHYSICS, 2013)
In this paper, we study 2-dimensional finite cellular automata defined by hexagonal local rule with periodic boundary over the field Z(3). We construct the rule matrix corresponding to the hexagonal cellular automata. For some given coefficients and the number of columns of hexagonal information matrix, we prove that the hexagonal cellular automata are reversible. DOI: 10.12693/APhysPolA.123.480
Keywords: CRYPTOGRAPHY; Physics